Peculiarities of Glis glis (Gliridae, Rodentia) monitoring in nest boxes on the eastern periphery of the range - Vekhnik, Victoria A.; Vekhnik, Vladimir P. (Nature Conservation Research: Заповедная наука, 2025)
Evaluation of the population dynamics of threatened species is one of the main purposes of Protected Areas. Regular monitoring of the Glis glis population using nest boxes has been conducted during eight years in the Zhiguli State Nature Biosphere Reserve, Russia. The purpose of the study was to summarise the results obtained during the monitoring in nest boxes and the advantages and disadvantages of the used method practised in this Protected Area for the first time in comparison with live-trap studies. Two hundred nest boxes were installed in ten lines. Nest boxes were checked twice a month in 2016–2021 and once a month in 2022–2023. The data on 452 adult individuals and 73 litters were obtained. The number of Glis glis individuals in nest boxes strongly depended on the seasonal activity, lasting from May–June till September–October in various years. The occupancy rate ranged from 27% to 60%. The maximal number per one check (42 individuals) was observed in July 2022. The lowest population count across all years was recorded in the first year after nest box installation, with a maximum of 16 individuals observed. A strong correlation was found between the total number of captured adults and the number of nests. Therefore, both indicators can be used for the evaluation of the abundance dynamics of Glis glis. In contrast to previous studies using live traps, we observed the year of reproductive failure only in 2023. The birth of juveniles in all registered mature females was observed in 2016 and 2018. In other years, the proportion of breeding females varied from 41.2% to 91.0%. Females reproduced from one to four times during their lifetime. The number of litters in nest boxes did not depend on the total reproduction intensity because of the high attractiveness of artificial nests for nursing posterity. The litter size was 4.7 ± 0.2 juveniles. The direct influence of weather conditions on the Glis glis reproduction and abundance dynamics was not confirmed. In general, using nest boxes makes it possible to evaluate the timing of reproduction and litter size, but distorts the age and sex structure and the ratio of reproducing and non-reproducing animals. Therefore, a combination of various methods is necessary for comprehensive population analysis.